2004
DOI: 10.1063/1.1739164
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic inhomogeneities in mixed-valence manganites

Abstract: It is suggested that extrinsic inhomogeneities in mixed-valence manganites deserve more attention and they should be taking into account on equal footing with hypothetical phase separation while examinating experimental data and developing the theoretical models of influence of stoichiometric and other types of inhomogeneities on properties of these and other transition-metal oxides.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…As mentioned previously, in an earlier study on the polycrystalline samples for x = 0.5, the resistivity showed metal-like behavior for B > 12 T [12]. Figure 3a shows evidence for this behavior for x = 0.52 and B = 5 T. This finding and the differences in strength of the magnetic field that induces metallic state also show that the conditions during sample preparations influence their physical properties as already shown in other systems [2,4,10].…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…As mentioned previously, in an earlier study on the polycrystalline samples for x = 0.5, the resistivity showed metal-like behavior for B > 12 T [12]. Figure 3a shows evidence for this behavior for x = 0.52 and B = 5 T. This finding and the differences in strength of the magnetic field that induces metallic state also show that the conditions during sample preparations influence their physical properties as already shown in other systems [2,4,10].…”
Section: Introductionsupporting
confidence: 79%
“…Here we have to point out that transport properties of the La 1−x Ca x MnO 3 (0.5 ≤ x < 1) polycrystalline samples were studied in magnetic fields up to 14 T by other authors [12] and it was shown that for x = 0.5 the resistivity shows metal-like behavior for B > 12 T, while for higher concentrations this behavior was not found up to 14 T. Note that when these materials are prepared in the form of thin films (which typically show higher crystalline order) their properties can be different with respect to the bulk materials (that are polycrystalline samples typically showing the crystalline disorder) [10,11,13,14]. In short, we will mention the most important results obtained on La 1-x Ca x MnO 3 manganites related to bulk material and films.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It was shown by many theoretical works that the ground states of manganite models tend to be intrinsically inhomogeneous due to the presence of strong tendencies toward phase separation [4]. Belevtsev [44] suggested that in addition to phase separation, the unavoidable influence of extrinsic inhomogeneities in mixed-valence manganites should always be taken into account when considering the experimental data and developing theoretical models for mixed-valence manganites. at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In com pounds in which the Griffith phase is detected, T C depends on the composition when one ion is substi tuted by another. Therefore, the existence of a Griffith phase is called into question [14][15][16][17]. It is assumed that the reasons are the technological crystal fabrica tion processes and that intrinsic inhomogeneities can not be distinguished from extrinsic ones [15].…”
Section: Introductionmentioning
confidence: 99%